Household Bargaining and Excess Fertility: An Experimental Study in Zambia - Ashraf, Nava; Field, Erica; Lee, Jean (American Economic Review, 2014)
We posit that household decision-making over fertility is characterized by moral hazard since most contraception can only be perfectly observed by the woman. Using an experiment in Zambia that varied whether women were given access to contraceptives alone or with their husbands, we find that women given access with their husbands were 19 percent less likely to seek family planning services, 25 percent less likely to use concealable contraception, and 27 percent more likely to give birth. However, women given access to contraception alone report a lower subjective well-being, suggesting a psychosocial cost of making contraceptives more concealable. (JEL C78, D12, D82, I31, J13, J16, O15)